The structural weaknesses of TTIP: Transatlantic partnership threatens more than just consumer protection - Heribert Dieter (Stiftung Wissenschaft und Politik (SWP), 2014)
Questions concerning consumer rights have thus far dominated discussions about the planned Transatlantic Trade and Investment Partnership (TTIP). This is surprising, because very much more is at stake. Firstly, TTIP and similar large-scale projects endanger the future of the multilateral trading order. Secondly, before the agreement can be signed, enormous and as yet entirely unexplored obstacles will need to be overcome; this includes the question of inter-state dispute settlement. The economic benefits of TTIP will also be smaller than claimed, whereas the long-term political damage, especially for Germany, could be considerable. (SWP Comments)
Keywords: 320